Radiation dose to the cochlea and its association with sensorineural hearing loss in head and neck cancer-A prospective study - Apoorva, K.V.; Vijendra Shenoy, S.; Athiyamaan, M.S.; Kabekkodu, Sushmitha; Kshithi, K.; Zuturu, Neehal (American journal of otolaryngology, 2023)
To determine the effect of cochlear dose on sensorineural hearing loss in patients with head and neck cancer treated by radiotherapy and chemoradiotherapy. A two-year longitudinal study was conducted on 130 subjects with various head and neck malignancies who were receiving radiotherapy or chemoradiation. 56 patients received only radiotherapy while 74 patients received concurrent chemoradiation five days a week at a dose of 66–70 Gy. They were categorized as having a radiation dose to the cochlea of <35 Gy, <45 Gy or >45 Gy. Pre- and post-therapy audiological evaluation was done using a Pure-tone audiogram, distortion product otoacoustic emission, and impedence. Hearing thresholds were measured at frequencies up to 16,000 Hz. Out of 130 patients 56 received RT alone and 74 received CTRT. There was statistically significant (p value <0.005) difference in Pure-tone audiometry assessment in both the RT and CTRT groups between subjects who received more than and <45 Gy of radiation to the cochlea. There was no significant difference in distortion product otoacoustic emission assessment between patients who received >45 Gy and <45 Gy radiation to the cochlea. Comparison between subjects who received radiation dose of <35 Gy and >45 Gy revealed significant results in the degree of hearing loss (p value <0.005). We observed that patients who received >45 Gy of radiation had more sensorineural hearing loss compared to patients who received <45 Gy. A cochlear dose of <35 Gy is associated with significantly lower hearing loss compared to higher doses. We would like to conclude by emphasizing the importance of regular audiological assessments prior to and post radiotherapy and chemoradiotherapy, with regular follow-ups encouraged over a longer period to improve the quality of life in patients with head and neck malignancy.